Triple botton line: Social, economic and enviromental into the Colombia - USA FTA (2019)
The objective of this paper is to demonstrate the presence that corporate social responsibility(CSR) have in the Free Trade Agreement between Colombia and the United States. This work was developed from the triple bottom line indicators proposed by the GRI (Global Reporting Initiative) from the social, economic and environmental results. For the present investigation, it was necessary to define the concept of FTA, by specifying the business relationship between Colombia and the United States and by outlining the concept of corporate social responsibility to complete an analysis of each of the 23 chapters of the text of the agreement, and its junctionwithmentionedindicators, and finding that only 12 of these chapters contain some CSR characteristics.